CNIB: Focus on the Future - ACO, CAO (Canadian Journal of Optometry, 2021)
In Canada, CNIB is the first place people turn to when they discover they are facing significant vision loss. CNIB helps people regain their independence by providing access to specialized rehabilitation services, innovative consumer products, and one of the world's largest libraries for people with print disabilities. Recently, the 88-year-old organization has made some changes, including a new brand and visual identity, as well as an exciting new approach to research.